2021
DOI: 10.1021/acsnano.1c10584
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Thermoelectrics Based on Solution-Grown SnSe Nanostructures

Abstract: Two-dimensional layered tin selenide (SnSe) has attracted immense interest in thermoelectrics due to its ultralow lattice thermal conductivity and high thermoelectric performance. To date, the majority of thermoelectric studies of SnSe have been based on single crystals. However, because synthesizing SnSe single crystals is an expensive, time-consuming process that requires high temperatures and because SnSe single crystals have relatively weaker mechanical stability, they are not favorable for scaling up synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Among the various TE materials reported so far, Co 4 Sb 12 -based filled skutterudites are getting considerable attention for their potential thermoelectric applications in the midtemperature range applications (500–750 K). A series of p- and n-type filled skutterudites with high ZT have been reported. Unfortunately, the highest ZT is achieved only in multiple rare-earth filled skutterudites (1.8 for n-type and 1.6 for p-type) so far. , Single rare-earth filled skutterudites still show lower ZT owing to its higher thermal conductivity, and moderate power factor.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various TE materials reported so far, Co 4 Sb 12 -based filled skutterudites are getting considerable attention for their potential thermoelectric applications in the midtemperature range applications (500–750 K). A series of p- and n-type filled skutterudites with high ZT have been reported. Unfortunately, the highest ZT is achieved only in multiple rare-earth filled skutterudites (1.8 for n-type and 1.6 for p-type) so far. , Single rare-earth filled skutterudites still show lower ZT owing to its higher thermal conductivity, and moderate power factor.…”
Section: Introductionmentioning
confidence: 99%
“…Solution-based methods, including the hydrothermal method, 35,36 solvothermal method 37,38 and aqueous solution method, 39,40 usually involve lower reaction temperatures and shorter reaction times. 41 In the solvothermal method, localized lattice distortions, strains, dislocations and nanoscale vacancies have been introduced into Cd-doped SnSe, resulting in a peak ZT of 1.7 at 823 K. 38 SnS 0.1 Se 0.9 nanoplates were obtained by a facile solution synthesis and achieved a peak ZT of 1.16 at 923 K. 42 Solution-processed SnSe–CdSe nanocomposites showed a peak ZT of 2.2 at 786 K by surface engineering. 43 Achieving a high average ZT in a wide temperature range is significant since thermoelectric devices are often required to operate under a large temperature gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Most SnSe fabricated by solution methods possess high ZT values that are limited to an elevated temperature range but have low average ZT values over the whole temperature range, which results in low thermoelectric power conversion efficiencies. 41 Improvement of the average ZT needs the synergistic optimization of the thermal- and electrical-transport properties over a temperature range as wide as possible. Manipulating porosity has proved to be an effective approach to enhance the phonon scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al reported a peak ZT value of 2.6 at 923 K for single crystal SnSe along the b -axis . However, it is difficult for the single crystal SnSe in thermoelectric devices to be applied, considering its poor mechanical properties, high preparation cost, and complex preparation process. , The optimization of thermoelectric properties for polycrystalline SnSe has always been a research hotspot, because of its better application prospects. The strategies that can enhance the thermoelectric performance are band structure engineering and microstructure manipulations. The ZT value was obtained from 0.3 at 773 K to 3.1 at 783 K 2 for p-type polycrystalline SnSe, after nearly a decade of efforts.…”
Section: Introductionmentioning
confidence: 99%